AB0618 A SNAPSHOT OF DISEASE ACTIVITY IN PATIENTS WITH BEHCET'S SYNDROME: PREDICTIVE FACTORS AND RELATIONSHIP WITH QUALITY OF LIFE. (June 2019) - Talarico, Rosaria; Parma, Alice; Zera, Eralda; Calabresi, Emanuele; Tani, Chiara; Baldini, Chiara; Mosca, Marta
Abstract : Background: Behçet's Syndrome (BS) is globally characterized by a variable spectrum of disease profile: while prevalent muco-cutaneous lesions and arthritis represent the only clinical features in patients with a benign disease subset, there are other patients who develop potentially sight or life-threatening manifestations, due to ocular, neurological or major vascular involvement. Beside the organ involvement, demographic factors could considerably influence the long-term and short-term outcomes of BD Objectives: The primary aim of the study was to evaluate disease activity in a cohort of BS patients consecutively followed in a BS clinic of a tertiary centre; the secondary aims were to identify potential predictive factors of disease activity and to compare disease activity with quality of life. Methods: One-hundred and thirty patients (71 males and 59 females; mean age 42±8 years, mean disease duration 11±4) with a diagnosis of BS according to the ISG criteria were studied. Disease activity has been evaluated by BDCAF and quality of life by the Short form (SF) 36. Patients were also categorized in major or minor involvement of BS according or not to the presence of ocular, neurological and vascular involvement in the course of disease Predictors of long-term outcome were identified by univariate analysis using the log-rank test and by multivariate analysis using Cox proportional hazards regression models. Results: At time of the evaluation, 39% of BS patients presented an active disease. Thirty-six patients presented muco-cutaneous involvement, 21 ocular disease, 10 joint involvement, 6 neurological impairment and 4 gastro-enteric involvement. Sixty-two percent of patients presented in the course of the disease a severe BS involvement and, among these, the majority was represented by males HLAB51 positive patients. The major limitations of quality of life related to disease activity were represented by vitality, physical functioning, bodily pain, general health perception. Conclusion: Younger men patients affected by BS are more suitable to have a more severe disease, due to an increased frequency both of morbidity and mortality, secondary to ocular, vascular and neurological involvement. The variable prognosis associated to different gender or age, may represent an essential and useful element to tailor the management not only to the type and severity of symptoms, but also to the epidemiological profile of BD patients. Disclosure of interests: Rosaria Talarico: None declared, alice Parma: None declared, Eralda Zera: None declared, Emanuele Calabresi: None declared, Chiara Tani: None declared, Chiara Baldini: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB